DUMAGUETE CITY HIGH SCHOOL: AN INSTITUTIONAL HISTORY, 1967-2019. - Saycon, Jojie (IJRDO- Journal of Educational Research, 2022)
This historical undertaking, which is borne out of the need to address the scarcity of localhistorical narrative traces and re-constructs the highlights of events at Dumaguete City HighSchool as a premier Secondary school in the division of Dumaguete City starting from its inceptionby virtue of a city ordinance to the enumeration of the different school offerings and programsfrom school year 1967 to 2019, the identification of the former and present school administrationare also given emphasis, as well its achievement and contribution, the challenges and how theyresponded to the challenges. The data were collected and subjected through documentary researchand identification of key informants by means of interview and external criticism.The establishments of Dumaguete City High School is a concreate manifestation of thedifferent factors. The significant role of the political leaders of the time serves as cornerstone inthe early beginnings of the school as indicated in the numerous city resolutions and ordinances andthe social impact of the creation of a City High School in Dumaguete City where we can see aclear and transparent collective and harmonious relationships with its local leaders and theimmediate community with the interaction of the achievements and contributions as well as thechallenges of the school heads, thus giving each school leaders the academic maneuvering on itsresponses.These political and social horizons as well as the leadership style of its school’s heads arenot different from each other, rather they are interconnected and very relevant as a determiningfactors in the establishment, operation and historical highlights of Dumaguete City High School.